2018
DOI: 10.1073/pnas.1800098115
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose crystals plastify by localized shear

Abstract: SignificanceWhile most attention has so far been devoted to the tensile properties of crystalline cellulose, the main elementary building block of plants, we show here using atomistic simulations that their shear is also an important mode of deformation, occurring at stress levels lower than tension with much larger ductility. We also demonstrate how crystalline defects like dislocations drastically facilitate plasticity. This analysis can be used as a basis for the micromechanical modeling of cellulose microf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 52 publications
2
27
0
Order By: Relevance
“…This is surprising as especially short CNCs are often considered as rigid and straight bodies thanks to their high axial elastic modulus. However, as recently reported, based on computational simulations, 34,35 cellulose crystals can be considered as flexible in their transverse and diagonal directions, which may lead to crystals deformation in such a waving manner along their axes.…”
Section: Discussionmentioning
confidence: 81%
“…This is surprising as especially short CNCs are often considered as rigid and straight bodies thanks to their high axial elastic modulus. However, as recently reported, based on computational simulations, 34,35 cellulose crystals can be considered as flexible in their transverse and diagonal directions, which may lead to crystals deformation in such a waving manner along their axes.…”
Section: Discussionmentioning
confidence: 81%
“…Indeed, recent simulations have suggested that plastic deformations due to high shear may occur even in crystalline cellulose. [ 71 ]…”
Section: Recent Progress In the Fundamental Understanding Of Nanocellmentioning
confidence: 99%
“…Then, the following large strain would trigger the deformation of the CNF network at microscale and even the shear behavior of cellulose nanocrystals at nanoscale. Recent simulation studies demonstrated that breaking and reformation of interfiber hydrogen bonds as well as the dihedral rotation are nonnegligible mechanisms in the origin of outstanding mechanical properties of cellulose nanocrystals (38,39). At last, the larger compression strain re sults in the densification of CNFP (CNF network at microscale).…”
Section: Impact Resistancementioning
confidence: 99%